EFFECT OF SPRAYING WITH ASCORBIC ACID AND TOCOPHEROL ON THE GROWTH AND YIELD OF BREAD WHEAT, TRITICUM AESTIVUM L. (British Journal of Global Ecology and Sustainable Development, 2023)
A field experiment was carried out at the Agricultural Research and Experiment Station affiliated with the College of Agriculture - University of Basra during the winter of 2021-2022. To study the response of growth and yield of bread wheat to spraying with ascorbic acid and tocopherol. The study included spraying four concentrations of ascorbic acid 0.150. 300. 450 mg l-1 was given the codes A0, A1, A2, A3, and four concentrations of tocopherol acid were sprayed, which are 0. 100. 200. 300 mg l-1 has been given the symbols T0, T1, T2, T3. The experiment was applied according to a randomized complete block design (R.C.B.D) using a factorial experiment method with three replications, where wheat seeds (Bohooth-22) were sown on 15.11.2021 at a seeding rate of 140 kg ha-1.